A novel analytical approach to study the charging characteristics of a shell and tube thermal energy storage system. Issue 1 (5th October 2021) - Agrawal, Abhishek; Kumar, Ashish; Rakshit, Dibakar
Abstract: This study presents a novel analytical solution of the phase change problem in a shell and tube arrangement of latent heat thermal energy storage (LHTES) system. The transient melting behavior of phase change material (PCM) is captured using time‐dependent boundary conditions and moving interface energy equation. An approximate mathematical model is developed with the help of dimensionless number (η), exponential integral function, Lambert W function, and Swamee and Oijha approximation. The proposed analytical solution is used for investigating the thermal performance of low, medium, and high melting temperature PCM for building, solar absorption cooling, and concentrated solar power (CSP) applications, respectively. The results obtained from the analytical approach are compared with a numerical model based on the enthalpy method. It is found that the root mean square difference between the average PCM temperature obtained from analytical solution and detailed numerical analysis is 3.3°C, 1.2°C, and 0.1°C for the low, medium, and high‐temperature systems, respectively. The temporal variation of melt front position and the effect of inner tube temperature are further investigated using the analytical solution. The mathematical model could be proposed as an effective tool for the assessment of shell and tube LHTES systems.